Symplocos ståhlii Kottaim., a new name for extant Symplocos globosa B.Ståhl (Symplocaceae) - Kottaimuthu, Ramalingam (Phytotaxa, 2018)
Symplocos Jacquin (1760: 24) is the largest genus in the family Symplocaceae and comprises about ca. 340 species (Fritsch et al. 2008). It is distributed in the tropical and subtropical regions of eastern and southeastern Asia, the Americas and Australia (Nooteboom 2004). The genus Symplocos Jacq. is known to have 33 species in Ecuador (Ståhl 2010; Ulloa et al. 2015), the majority of which occur in Andean forests (Ståhl 1995). While revising the genus Symplocos in Ecuador, Ståhl (1991) described 15 new species. Among these, the name S. globosa B.Ståhl (1991: 27) is illegitimate, being a later homonym (Art. 53.1 of the ICN; McNeill et al. 2012) of the fossil taxon S. globosa R. Ludwig (1857: 98). Therefore, the new name Symplocos ståhlii Kottaim. is proposed here as a replacement name for the extant S. globosa.